2011
DOI: 10.1039/c0mb00294a
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide RNAi screen identifies novel targets of neratinib sensitivity leading to neratinib and paclitaxel combination drug treatments

Abstract: ErbB2 is frequently activated in tumors, and influences a wide array of cellular functions, including proliferation, apoptosis, cell motility and adhesion. HKI-272 (neratinib) is a small molecule pan-kinase inhibitor of the ErbB family of receptor tyrosine kinases, and shows strong antiproliferative activity in ErbB2-overexpressing breast cancer cells. We undertook a genome-wide pooled lentiviral RNAi screen to identify synthetic lethal or enhancer (synthetic modulator screen) genes that interact with neratini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 59 publications
1
27
0
Order By: Relevance
“…These results, as well as those of the study from Seyhan et al28 point to the potential added benefit of using neratinib as a combinational treatment option alongside other targeted treatments as well as conventional chemotherapeutics.…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…These results, as well as those of the study from Seyhan et al28 point to the potential added benefit of using neratinib as a combinational treatment option alongside other targeted treatments as well as conventional chemotherapeutics.…”
Section: Introductionmentioning
confidence: 54%
“…In a study using a panel of cell lines, we showed that the response to neratinib was correlated with baseline HER2 and phosphorylated HER2 levels, but not with EGFR levels in vitro 26. Interestingly, neratinib decreased the activation of phosphatidylinositide 3-kinase and mitogen-activated protein kinase downstream pathways, and the activity against AKT and ERK could be correlated with efficacy 14,26,28. Other biomarker candidates that have been investigated in vitro include upregulation of RB1CC1, HER3, FOXO3a, and NR3C1 as well as downregulation of CCND1 mRNA, all of which have been correlated with response to neratinib 29.…”
Section: Introductionmentioning
confidence: 96%
“…The 16-week PFS rate was 45%, and the median PFS duration was 19 weeks. It is noteworthy that the findings of Seyhan et al (2011) support a phase III clinical trial of neratinib with paclitaxel among patients with breast cancer. Three large phase III clinical trials using neratinib are currently ongoing.…”
Section: Introductionmentioning
confidence: 58%
“…Recently, preclinical data have shown that lapatinib is a substrate of multidrug efflux transporter P-glycoproetin (ABCG1), which is located at the BBB and may account for the decreased CNS penetration of lapatinib [71]. Studies have shown that neratinib can reverse ABCG1-mediated multidrug resistance [72] and it was unaltered by the presence of ABCG2 transporter [73]. Based on these results, neratinib has the potential to pass BBB and effectively treat CNS metastasis.…”
Section: Neratinibmentioning
confidence: 93%